Experimental Investigation of Cement/Soda Residue for Solidification/Stabilization of Cr-Contaminated Soils. (25th July 2020) - Zha, Fusheng; Zhu, Fanghua; Kang, Bo; Xu, Long; Deng, Yongfeng; Yang, Chengbin; Chu, Chengfu
Abstract : Adopting more efficient and sustainable remediation materials is of great importance for the development of solidification and stabilization (S/S) technology. Among them, soda residue could be considered as a desirable binder due to its strong adsorption for heavy metals. For understanding of the performance of Cr-contaminated soils treated by cement/soda residue, the strength, leaching and microstructural characteristics, and the long-term effectiveness under wetting-drying cycles were comprehensively investigated in this study. The results showed that the unconfined compressive strength (UCS) increased and the leached Cr 3+ concentration decreased with curing time, binder content, and binder ratio. Increasing the soda residue from C6S14 to C6S24 could improve soil strength and reduce leachability of Cr 3+, while a reverse trend was presented with increasing initial Cr 3+ concentration. With subsequent wetting-drying cycles, the UCS further increased and then decreased; inversely, the leached Cr 3+ decreased, followed by an increase of Cr-contaminated soils. For the specimens of C6S14 and C6S24, the maximum UCS of 6.04 MPa and 6.48 MPa was reached; correspondingly, the minimum leached Cr 3+ concentration of 2.78 mg/L and 1.93 mg/L was reached after 3 wetting-drying cycles, respectively. Microstructure analysis results found that reaction products like calcium silicate hydrate (C-S-H) and ettringite (AFt) increasingly occupied the soil pore space and caused a denser soil structure after 3 wetting-drying cycles, which indicated the long-term effectiveness of contaminated soils treated by cement/soda residue.